Benthic Macroinvertebrates and Trichoptera Adults for Bioassessment Approach in Streams and Wadeable Rivers in Lao People's Democratic Republic - SRIPANYA, JUTAMAS; RATTANAWILAI, KWANSIRI; VONGSOMBATH, CHANDA; VANNACHAK, VIENGKHONE; HANJAVANIT, CHUTIMA; SANGPRADUB, NARUMON (Tropical Natural History, 2022)
Rapid bioassessment for water quality has not been established in Loa PDR. This study provides baseline information on the composition and distribution of benthic macroinvertebrate diversity and Trichoptera adults in two streams and three wadeable rivers for future rapid bioassessment in Lao PDR. Benthic macroinvertebrates were collected at each site in 20 sweeps using a D-Frame net (450 µm mesh size) in April 2017, 2018, and November 2017. Adults of Trichoptera were collected using an ultraviolet light trap. A total of 4,539 benthic macroinvertebrates belonging to 176 taxa, 84 families, 15 orders, and 3 phyla were found. Ephemeroptera and Trichoptera were the two orders with the most taxa richness and abundance. A total of 160 species in 16 families of Trichoptera adults were found. Leptoceridae and Hydropsychidae were diverse and abundant family. Agricultural activities had altered water to high electrical conductivity, high total dissolved solids and increased nutrient input even though almost all sampling sites were classified by the National Water Quality Standard as good water quality. Total taxa richness of benthic macroinvertebrates decreased with increasing disturbance. In contrast, high electrical conductivity and total dissolved solids at Nam Hinboun, a preserved area with no human disturbance exhibited the natural characteristics of a karst river. Canonical Correspondence Analysis revealed that physical variables, especially water velocity and water depth, determined benthic macroinvertebrate assemblages rather than chemical variables. The composition and distribution of Trichoptera larvae were determined by their species-specific ecological requirements. Benthic macroinvertebrate assemblages could respond to physico-chemical variables of streams better than the EPT taxa or Trichoptera taxa (both larvae and adults) and using macroinvertebrate assemblages to detect change in streams is promising.